The Social Utility of Ambivalence: Being Ambivalent on Controversial Issues Is Recognized as Competence - Pillaud, Vincent; Cavazza, Nicoletta; Butera, Fabrizio (Frontiers in Psychology, 2018)
Research on attitudinal ambivalence is flourishing, but no research has studied how others perceive its expression. We tested the hypothesis that the expression of attitudinal ambivalence could be positively valued if it signals careful consideration of an issue. More specifically, ambivalence should be judged higher on social utility (competence) but not on social desirability (warmth), compared to clear-cut attitudes. This should be the case for controversial (vs. consensual) issues, where ambivalence can signal some competence. The participants in four experiments indeed evaluated ambivalence higher on a measure of social utility, compared to clear-cut (pro-normative and counter-normative) attitudes, when the attitude objects were controversial; they judged pro-normative attitudes higher for both social utility and social desirability when the attitude objects were consensual. Attitudinal ambivalence can therefore be positively valued, as it is perceived as competence when the expression of criticism is socially accepted.